2012
DOI: 10.1007/bf03262882
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional microhardness of bovine enamel subjected to three paediatric liquid oral medicines: an in vitro study

Abstract: Antibiotic G1 (Klaricid®) presented an in vitro protective effect against acid attacks probably due to its mineral content and viscosity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…() and Soares et al . () also found higher mineral loss in dental fragments submerged in deionized water when compared with other substances, among them, an antimicrobial agent (clarithromycin). The referred authors suggest that the cariogenic/erosion challenge suffered by the teeth probably occurred because the calcium and phosphate ions in enamel were released due to water subsaturation.…”
Section: Resultsmentioning
confidence: 85%
“…() and Soares et al . () also found higher mineral loss in dental fragments submerged in deionized water when compared with other substances, among them, an antimicrobial agent (clarithromycin). The referred authors suggest that the cariogenic/erosion challenge suffered by the teeth probably occurred because the calcium and phosphate ions in enamel were released due to water subsaturation.…”
Section: Resultsmentioning
confidence: 85%
“…Other in vitro studies have also demonstrated that Claritin® may reduce enamel hardness (18)(19)(20) and increase surface roughness (17). In the present study, the varnishes were applied once and removed after 6 h of application to simulate the clinical condition, since the emphasis was allowing the chemical effect of the varnish components, rather than the mechanical protection.…”
Section: Discussionmentioning
confidence: 98%
“…It is worth noting that from a depth of 120 µm, the bleaching agent, as well as the demineralizing solution, had no influence on CSH, possibly because of the distance to the outer surface (22). Another important factor to be observed is the change of the product pH.…”
Section: Discussionmentioning
confidence: 99%